Evaluation of Hepatoprotective Activities of Bryophyllum pinnatum Leaf Extract in Paracetamol Induced Toxicity in Wistar rats - Odangowei Ogidi; Happiness Orlu; Blessing Poripo (Trends in Pharmaceutical Sciences)
Paracetamol-induced hepatotoxicity poses a significant health risk. Bryophyllum pinnatum (commonly known as "Never Die") has traditional medicinal applications, including potential hepatoprotective effects. This study evaluated the protective effects of B. pinnatum leaf extract on paracetamol-induced liver toxicity in Wistar rats. Five groups were examined: a normal control, a paracetamol-only group (2 g/kg), two treatment groups receiving paracetamol with 200 mg/kg or 400 mg/kg B. pinnatum extract, and a standard control treated with 200 mg/kg vitamin E. After two weeks, blood samples were analysed for liver enzymes and antioxidant biomarkers. Paracetamol significantly elevated AST, ALT, ALP, LDH, and creatinine levels (p<0.05), indicating liver damage. Rats treated with 400 mg/kg B. pinnatum extract showed marked reductions in AST (94.48±3.38 U/L), ALT (79.74±4.12 U/L), and LDH (15.36±0.64 U/L), comparable to vitamin E treatment. Antioxidant markers were also altered: SOD, catalase, and GSH levels decreased in the paracetamol group, while MDA increased significantly. Treatment with 400 mg/kg B. pinnatum improved these parameters—SOD (5.90±0.17 U/mg protein), catalase (4.49±0.24), GSH (5.75±0.44), and MDA (2.85±0.18)—indicating restored oxidative balance. These effects mirrored those observed in the vitamin E-treated group. The study concludes that B. pinnatum extract, particularly at higher doses, offers significant hepatoprotective and antioxidant effects against paracetamol-induced liver damage. This supports its potential use in managing drug-induced hepatic injury.